Association of objective and subjective parameters of obstructive sleep apnea with plasma aldosterone concentration in 2,066 hypertensive and 25,368 general population - Wang, Hui; Heizhati, Mulalibieke; Li, Nanfang; Gan, Lin; Lin, Mengyue; Yang, Wenbo; Li, Mei; Yao, Ling; Liu, Miaomiao; Maitituersun, Adalaiti; Liu, Shasha; Wu, Zihao; et al. (Frontiers in Endocrinology, 2023)
Study Objectives: OSA severity has been suggested in aldosterone elevation in resistant hypertension, whereas undetermined in the rest. We explored association of OSA parameters with plasma aldosterone concentration (PAC) in participants with and without hypertension. Methods: We enrolled clinical hypertensives with polysomnography and PAC data under no interfering agents, compared (log) PAC and assessed linearity of log-PAC by tertiles (T1/2/3) of sleep parameters, and their association using linear regression by gender and age. We enrolled participants with and without hypertension who had No-SAS scale and PAC data from community, and duplicated the observations from clinical setting considering age, gender and presence of hypertension. Results: Of 2066 clinical patients with hypertension (1546 with OSA), men participants (n=1412), log apnea-hyponea index (P=0.043), apnea index (AI, P=0.010) and lowest oxygen saturation (LSaO2, P=0.013) showed significant linearity with log PAC. Log-AI (B=0.04, 95%CI: 0.01,0.07, P=0.022) and log-LSaO2 (B=-0.39, 95%CI: -0.78,-0.01, P=0.044) showed significant positive and negative linear association with log PAC in regression. In community dwellers, 6417 participants with untreated hypertension (2642 with OSA) and 18951 normotensive participants (3000 with OSA) were included. Of men participants with and without hypertension, OSA group showed significantly higher (log) PAC than did their counterparts and log-NoSAS score showed positive association with log-PAC (hypertension: B=0.072, 95%CI: 0.002,0.142, p=0.043; normotension: B=0.103, 95%C I: 0.067,0.139, P<0.001) in linear regression analysis, which were consistent in all age groups. Conclusions: OSA parameters were positively associated with PAC in normotensive and hypertensive participants, indicating that OSA may increase circulating aldosterone, specially in men.